2006
DOI: 10.1007/s00167-006-0116-8
|View full text |Cite
|
Sign up to set email alerts
|

Bioabsorbable screw divergence angle, not tunnel preparation method influences soft tissue tendon graft-bone tunnel fixation in healthy bone

Abstract: Bone tunnel fixation of a soft tissue tendon graft is the weak link immediately following ACL reconstruction. This biomechanical study evaluated the influence of extraction drilled or step dilated bone tunnels and bioabsorbable screw divergence on soft tissue tendon graft fixation. From an initial group of 50 available specimens, similar apparent bone mineral density porcine tibiae (1.2 +/- 0.24 g/cm2) were divided into two groups of ten specimens each. Group 1 (extraction drilled) received 9 mm diameter tunne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…If this proves true, then we would be able to avoid tunnel convergence, and the reduced angle could help with the fixation strength as well because it is reported that the fixation strength decreases as the fixation angle increases. 11 This study demonstrated that the safe distances were approximately 30 mm to the ACL tunnel proximally in LCL reconstruction. Within the safety ranges of angles, possible distances that would not violate the far cortex would be longer; however, we believe that it would be safer if we make sure that 30 mm is not exceeded in drilling.…”
Section: Discussionmentioning
confidence: 93%
“…If this proves true, then we would be able to avoid tunnel convergence, and the reduced angle could help with the fixation strength as well because it is reported that the fixation strength decreases as the fixation angle increases. 11 This study demonstrated that the safe distances were approximately 30 mm to the ACL tunnel proximally in LCL reconstruction. Within the safety ranges of angles, possible distances that would not violate the far cortex would be longer; however, we believe that it would be safer if we make sure that 30 mm is not exceeded in drilling.…”
Section: Discussionmentioning
confidence: 93%
“…The specially designed clamp enabled the servohydraulic device (MTS 858, Eden Prairie, MN) tensile loading vector to be aligned directly with the tunnel (Fig. 2) [16][17][18]. This direct tensile load on the looped soft tissue tendon graft provided a "worst case" loading scenario.…”
Section: Methodsmentioning
confidence: 99%
“…Porcine tibiae were however screened for BMD using DXA scanning to better simulate human tibia. Previous soft tissue ACL graft fixation studies have found porcine soft tissue grafts [17,18] and tibiae [16][17][18] to be more representative of young human tissue than cadaveric tissues.…”
Section: Limitationsmentioning
confidence: 99%
“…3,10 However, divergence between the screw and the bone plug in the femoral tunnel can diminish fixation strength. 6,9,13,15,19 In laboratory tests, divergence between the screw and bone plug of 20° has been necessary to diminished fixation strength. 6,9,13,19 For transtibial drilling, multiple strategies have evolved to limit screw-graft divergence, including hyperflexion of the knee during screw insertion.…”
mentioning
confidence: 99%
“…6,9,13,15,19 In laboratory tests, divergence between the screw and bone plug of 20° has been necessary to diminished fixation strength. 6,9,13,19 For transtibial drilling, multiple strategies have evolved to limit screw-graft divergence, including hyperflexion of the knee during screw insertion. 2,7,11,16,18,20 There has been less research on limiting divergence with anatomic femoral tunnels.…”
mentioning
confidence: 99%